Integrating Science and Religion at Malaysian and Indonesian Higher Education - Mohammad Hidayaturrahman; Sudarman Sudarman; Husamah Husamah; Ita Rahmania Kusumawati (AT-TA'LIM, 2021)
This article analyzes the integration model between science and religion in Malaysian and Indonesian Higher Education. So far, the dichotomy of science and religion is considered to be one of the causes for the exit of the Islamic world from the Western world. In this century, educational institutions in the Islamic world began to re-select the integration pattern of science. This study uses qualitative methods, by collecting data through observation, visiting two higher education institutions studied, and conducting in-depth interviews with relevant parties, namely the International Islamic University Malaysia (IIUM) in Malaysia and Universitas Muhammadiyah Malang (UMM) in Indonesia. Data collection is also done by searching documents and referral sources in various data sources available online. From the research conducted, it was found that, integration carried out by Islamic universities in Malaysia and Indonesia was to open faculties and study programs without any religious or public claims. Everything is the same, and there are no restrictions on the rules for students based on religion to enter into it. So, education is inclusive, it can be for anyone. This model succeeded in advancing Islamic educational institutions.